MHD free convection of nanofluid in a cavity with sinusoidal walls by using CVFEM - Sheikholeslami, M.; Öztop, Hakan Fehmi (Elsevier, 2017)
Effect of external magnetic source on Fe3O4-water nanofluid convection in an enclosure with sinusoidal outer cylinder is reported. Final equations are solved by means of Control Volume based Finite Element Method (CVFEM). Roles of Rayleigh number (Ra = 10(3), 10(4) and 10(5)), Hartmann number (Ha = 0 to 15), amplitude of the sinusoidal wall (A = 0.1 to 0.2) and volume fraction of Fe3O4 (phi = 0 and 0.04) are reported. Results show that Lorentz forces cause the thermal plume to slant to left side. Impact of adding nanoparticle is more effective in high Hartmann number. Temperature gradient near the hot wall enhances with augment of buoyancy forces but it reduces with augment of Lorentz forces.
Keywords: Nanofluid; Magnetic source; Natural convection; CVFEM; Complex shaped wall